Wireless GINI: an educational platform for hosting virtual wireless networks. (13th April 2016) - Youssef, Ahmed; Maheswaran, Muthucumaru; Youssef, Lamis
Summary: We describe Wireless GINI, a wireless platform for hosting virtual networks. Wireless GINI Is Not Internet (GINI) allows each virtual network to define its own topology and network configuration, while amortizing costs by sharing the physical infrastructure. The platform also creates mechanisms to readily integrate physical wireless devices into a deployed network. The platform supports a diverse combination of network elements that are all integrated into one custom Internet. The platform seamlessly integrates process‐emulated components running on the user machine, wireless mesh overlays deployed on the wireless platform, and generic wireless devices connected to the user's custom network. Wireless GINI provides a user‐friendly interface that makes the physical setup process completely transparent to the user. A centralized server is used to provide this transparency, handle user requests, and automatically provision the shared physical infrastructure. We describe the design and implementation of Wireless GINI. Moreover, we evaluate the performance of the platform and suggest several educational experiments that can be conducted on this new platform. A detailed survey of the existing toolkits and platforms and a comparison with Wireless GINI are also provided. Copyright © 2016 John Wiley & Sons, Ltd.